New Triterpenoid from Novel Triterpenoid 15-O-Glycosylation on Ganoderic Acid A by Intestinal Bacteria of Zebrafish - Te-Sheng Chang; Chien-Min Chiang; Tzi-Yuan Wang; Chun-Hsien Lee; Yu-Wen Lee; Jiumn-Yih Wu (Molecules, 2018)
Functional bacteria that could biotransform triterpenoids may exist in the diverse microflora of fish intestines. Ganoderic acid A (GAA) is a major triterpenoid from the medicinal fungus Ganoderma lucidum. In studying the microbial biotransformation of GAA, dozens of intestinal bacteria were isolated from the excreta of zebrafish. The bacteria’s ability to catalyze GAA were determined using ultra-performance liquid chromatography analysis. One positive strain, GA A07, was selected for functional studies. GA A07 was confirmed as Bacillus sp., based on the DNA sequences of the 16S rRNA gene. The biotransformed metabolite was purified with the preparative high-performance liquid chromatography method and identified as GAA-15-O-β-glucoside, based on the mass and nuclear magnetic resonance spectral data. The present study is the first to report the glycosylation of Ganoderma triterpenoids. Moreover, 15-O-glycosylation is a new microbial biotransformation of triterpenoids, and the biotransformed metabolite, GAA-15-O-β-glucoside, is a new compound.